Specificity of representation of the military past in the russian commorative and revisionist cinema of the XXI century - A. P. Petrova (Концепт: философия, религия, культура, 2020)
Based on theoretical studies of the phenomenon of cultural memory (M. Halbwax, F.R. Ankersmit, J. Zerubavel), the author analyzes the essence and mechanisms of commemoration in contemporary Russian military-themed cinema. The relevance of the study is due to the wide public interest in domestic military cinema, its social significance and the growing number of commemorative practices (which include cinematographic works) in honor of the anniversary dates of victory in the Great Patriotic War. The empirical base of the study is founded on the analysis of broad Russian film distribution and the domestic film festival industry 2000-2019.Working with the phenomenon of the past, military cinema inevitably creates its on-screen interpretation, which, as a result of wide circulation, becomes an act of memory policy aimed at the formation and maintenance of social identity. In this connection, the aim of the study is to identify the axiological component of Russian military cinema of the 21st century by analyzing the value programs of the movie heroes. Tracing the essence and logic of the formation of the Soviet political «myth of war» in cinema, the author comes to the conclusion that this paradigm of war record representation is still present on the screen, taking the form of commemorative cinema. The axiological opposition to this trend is the segment of revisionist cinema, which does not reproduce the Soviet myth, but reinterprets and problematizes the events of the military past. The analysis of revisionist films reveals new options for representing the traumatic military experience on the screen. Finally, conclusions are drawn about the axiological component of commemorative and revisionist cinema.